Association between hypoparathyroidism and defective T cell immunity in 22q11.2 deletion syndrome. Issue 2 (12th February 2010) - Herwadkar, A; Gennery, A R; Moran, A S; Haeney, M R; Arkwright, P D
Abstract : Aims: Although poor thymic function leading to viral and fungal infections can be a feature of chromosome 22q11.2 deletion syndrome, most patients have relatively normal immunity. The aim of this study was to investigate which clinical and laboratory parameters best predict the likelihood of serious or recurrent infections in patients with this syndrome. Methods: Clinical and laboratory parameters from 64 patients with 22q11.2 deletion syndrome referred to two immunology centres in the north of England were studied retrospectively. Results: 31 (48%) patients had no problems with infection, 21 (33%) had bacterial infections, and 12 (19%) had recurrent or persistent thrush and/or viral enteritis and bronchiolitis, the latter suggestive of a significant T cell immunodeficiency. Patients with a history of thrush/viral infections, but not those with bacterial infections, had significantly lower CD4+ and CD8+ T lymphocyte numbers (relative risk (95% CI) 0.3 (0.1 to 0.8)) and phytohaemagglutinin mitogen responses (0.4 (0.2 to 0.8)) adjusted for age at testing. Hypoparathyroidism was associated with low T lymphocyte numbers and function (p<0.05) as well as an increased risk of thrush/viral infections (p<0.0001) after adjusting for age at testing. Conclusions: 22q11.2 syndrome patients with hypoparathyroidism are more likely to have a clinically significant T cell immunodeficiency and lower laboratory parameters of T cell function, with a higher risk of thrush and viral bronchiolitis and enteritis. Measurement of absolute CD3 count is a simple and accurate predictor of fungal/viral infection risk, with phytohaemagglutinin mitogen responses providing little or no further value in most patients.